Effect of Response Surface Methodology-Optimized Ultrasound-Assisted Pretreatment Extraction on the Composition of Essential Oil Released From Tribute citrus Peels - Li, Guoqiang; Liu, Shuxun; Zhou, Qingqing; Han, Jiarun; Qian, Cheng; Li, Yongquan; Meng, Xia; Gao, Xin; Zhou, Tao; Li, Ping; Gu, Qing (Frontiers in Nutrition, 2022)
The traditional hydrodistillation(HD) and ultrasound-assisted methods(UAE) were proposed to obtain essential oil (EO) from Tribute citrus(TC) peels. The Box-Behnken design was employed for the optimization of the traditional hydrodistillation and ultrasound-assisted extraction procedure. Moreover, GC-MS and Electronic nose (E-nose) were applied to identify the discrepancy of extraction methods. The yield of essential oil extracted by UAE(114.02 mg/g) was relatively higher than HD(85.67 mg/g) The optimum UAE conditions led to a significantly higher essential oil yield than that of HD. A total of 28 compounds were extracted from the TC peels as terpenes were the predominant components. D-limonene was the most vital compound in the Tribute citrus essential oil(TCEO) accounting for 86.38% of total volatile concentration in HD and 86.75% in UAE, respectively. The chart of radar and graphic of principal components analysis by E-nose displayed no significance, which was similar to GC-MS results. The present study demonstrated that UAE is an efficient method for Tribute citrus essential oil extraction, which provides a promising method for the separation of essential oil from aromatic plant materials.